The international handbook of public financial management - Allen, Richard; Hemming, Richard; Potter, B (Palgrave Macmillan, 2013)
The International Handbook of Public Financial Management is essential reading for governmental policy-makers, and practitioners and consultants working in this field, whose importance has been highlighted by the global financial crisis. It is a primary source for academics and students of economics, public finance, accountancy and public policy.